Reinventing Urban Planning and Building The Capacity For It - Nathaniel von Einsiedel (Journal of Regional and City Planning, 1996)
Entering  the  21st  century,  the  world  is  undergoing  a  rapid  change  in  many  aspects  of  life.  The emergence of a knowledge-based global economy has undermin ed old realities throughout the world, creating opportunities as well as problems. Without more effective urban planning, world cities will not  be  able  to  fully  benefit  from  these  opportunities.  More effective urban planning, as an integral component of urban management, is essential to avoid the breakdown of world cities.This  article  is  trying  to  present  the  fallacies  and  limitations  of  current  urban  planning  practice against  current  and  future  conditions,  and   to  provide  a  recipe  for  reinventing  effec tive  urban planning.